Analisis Keabsahan Penjualan Saham Pemegang Saham yang Dinyatakan Tidak Hadir dan Tidak Diketahui Keberadaannya (Afwezigheid) - Viena Viena; Hasim Purba; Mahmul Siregar (Jurnal Hukum Lex Generalis, 2025)
This research examines the legal uncertainty issues in share transfer of shareholders with afwezigheid status (absent and whereabouts unknown) which requires special management by the Heritage Property Office (Balai Harta Peninggalan/BHP) as the representative custodian of assets. Through normative juridical methods with statutory and case approaches, this research analyzes the share transfer case of PT. Asri Pembangunan Catur Karya Cipta and concludes that the transfer of afwezigheid shares by BHP is legally valid despite not being directly conducted by the rightful owner (eignaar), as BHP acts as custodian (bezit) representing the afwezigheid shareholder with obligations to obtain court permission and comply with Limited Liability Company Law procedures to avoid formal defects. Legal protection is available for afwezigheid shareholders or their heirs through the right to file lawsuits if they feel BHP's actions violate their rights and obligations, however the research recommends the need for regulatory updates given the limited regulations concerning afwezigheid to provide better legal certainty and protection.